A PANEL ARDL ANALSIS OF THE PRODUCTIVITY OF KEY ECONOMIC SECTORS CONTRIBUTING TO LOCAL ECONOMIC GROWTH IN AN EMERGING COUNTRY - GARIDZIRAI, Rufaro; MUZINDUTSI, Paul-Francois (Studia Universitatis Babeș-Bolyai Oeconomica, 2020)
It has become precise and indisputable that the South African economic growth has been stagnant. Despite this stagnant growth, the productivity of key sectors is supposed to alleviate some of the challenges of the South African economy. The aim of this study is to identify the key sectors that may assist in boosting economic growth at a local level. This study employed three estimators (PMG, MG and DFE) of a panel autoregressive distributed lag model (ARDL) to analyse the short- and long-run effects of various sectors’ productivity on economic growth in a South African district. By employing annual data from 1996 to 2015, 6 sectors (construction, finance, trade, community service, manufacturing, transport, mining and tourism) from four municipalities in South Africa were analysed. Results show that the productivity of the construction, transport, trade, manufacturing and finance sectors influence economic growth positively in the long-run. However, the productivity of the mining and tourism sectors negatively affect economic growth in the long-run. Short-run results reveal that, in the short-run, the productivity of all sectors, except trade and transport, contribute positively to local economic growth. This study recommends that the government improves the production methods and invests in infrastructure and skills development to advance the productivity of the mining and tourism sectors. JEL classification: O12, R11;